2007
DOI: 10.1124/jpet.106.107904
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase (COX)-1 and COX-2 Participate in 5,6-Epoxyeicosatrienoic Acid-Induced Contraction of Rabbit Intralobar Pulmonary Arteries

Abstract: Epoxyeicosatrienoic acids (EETs) have been reported to contract intralobar pulmonary arteries (PA) of the rabbit in a cyclooxygenase (COX)-dependent manner. In the present study, we observed that COX-1 and COX-2 isoforms were expressed in freshly isolated PA of healthy rabbits. We examined the hypothesis that both COX isoforms participate in 5,6-EET-induced contraction of rabbit intralobar PA. Selective inhibition of COX-1 with 300 nM 5-(4-chlorophenyl)-1-(4-methoxyphenyl)-3-(trifluoromethyl)-1H-pyrazole (SC-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The minor expression of COX-1 in the AA corroborates with previous work in rabbit vessels, such as femoral (28), intralobar pulmonary (20), carotid (17), and small mesenteric (32) arteries. The present study extends those previous studies by showing a similar COX-1 expression in the aorta of normal and atherosclerotic AA, which was mainly localized in the adventitia.…”
Section: Discussionsupporting
confidence: 78%
“…The minor expression of COX-1 in the AA corroborates with previous work in rabbit vessels, such as femoral (28), intralobar pulmonary (20), carotid (17), and small mesenteric (32) arteries. The present study extends those previous studies by showing a similar COX-1 expression in the aorta of normal and atherosclerotic AA, which was mainly localized in the adventitia.…”
Section: Discussionsupporting
confidence: 78%
“…S1, 5,6-, 8,9-, and to a lesser extent 11,12-EET were substrates in the presence of both enzymes, yielding measurable oxygen consumption over 25 s at 50 μM. 5,6-EET, reported to be a COX substrate (18,19), noticeably reacted with COX-1 and COX-2 at concentrations ranging between 15 and 50 μM (SI Appendix, Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…Although EETs are primarily metabolized by sEH, a few studies have observed that the 5,6-EET and 8,9-EET are substrates for COX-1 (17,18) and COX-2 (19). The COX metabolites of EETs have largely undefined biological activity, yet Homma et al determined that the ct-8,9-epoxy-11-hydroxy-eicosatrienoic acid (ct-8,9-E-11-HET) metabolite is a renal vasoconstrictor and potent mitogen, approximately three orders of magnitude more potent than its parent, 8,.…”
mentioning
confidence: 99%
“…All of the above-described phenotypic alterations may well be the result of alterations in the production, catabolism and/or function of eicosanoids: bioactive mediators derived from arachidonic acid via -6 fatty acids (including prostaglandins, prostacyclins, leukotrienes, thromboxanes, hepoxilins, and lipoxins) and bioactive mediators derived from eicosapentaenoic acid and docosahexaenoic acid via -3 fatty acids, (including resolvins, docosatrienes, eoxins, and neuroprotectins). Eicosanoids exert largely unappreciated complex control over virtually all physiological processes: inflammation (Chiang et al, 2005;Leone et al, 2007;Mariotto et al, 2007;Serhan, 2007;Seubert et al, 2007), resolution phase of inflammation (Serhan, 2007), innate immunity (Ballinger et al, 2007), cardiopulmonary and vascular functions (Moreland et al, 2007;Seubert et al, 2007), angiogenesis (Fleming, 2007;Inceoglu et al, 2007), sensor of vascular pO 2 (Sacerdoti et al, 2003), bowel motility (Proctor et al, 1987), regulation of lipid metabolism and insulin sensitivity (Larsen et al, 2007;Nigam et al, 2007;Spector and Norris, 2007), central nervous system functions (Miyata and Roman, 2005;Jakovcevic and Harder, 2007), modulation of non-neuropathic pain (Inceoglu et al, 2007), neurohormone secretion and release (Inceoglu et al, 2007), fibrinolysis (Westlund et al, 1991;Jiang, 2007), inhibition of platelet aggregation (Westlund et al, 1991;Jiang, 2007), reproductive success (Cha et al, 2006;Weems et al, 2006), blastocyst implantation (Cha et al, 2006;Kennedy et al, 2007), early embryonic as well as fetal development (Cha et al, 2006), stimulation of tyrosine phosphorylation (Chen et al, 1998), G protein-si...…”
Section: Discussionmentioning
confidence: 99%